2012
DOI: 10.17509/ijal.v2i1.71
|View full text |Cite
|
Sign up to set email alerts
|

Receptive and Productive Vocabulary Acquisition: Examining Processing Time and Memory Threshold

Abstract: Abstract:In the present research a picture card-based vocabulary study method was used to determine the pace of learner acquisition in terms of both receptive and productive knowledge. Fifty-eight first-year Japanese university students in two classes were used in the study. The subjects were placed into a single experimental group and both classes were taught by the researcher. During the treatment sessions the subjects studied fifteen vocabulary items chosen from the course textbook (Fifty-Fifty: A speaking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…However, most of the research investigating the impact of Quizlet and podcasting on students' vocabulary acquisition has used investigator-created or available material. Relatively little has been done to study the benefits of studentcreated podcasts and Quizlet flashcards, despite the fact that various studies have demonstrated the cognitive, affective and motivational benefits accrued to students' creating their own learning material (Gholami & Mohammadi, 2015;Hsu et al, 2008;Milliner, 2013;Nikolova, 2002;Oberg, 2012;Philips, 2017;Wong & Looi, 2010). For example, Nikolova (2002) investigated how effective vocabulary acquisition is when students participate in the creation of the learning material.…”
Section: Various Researches Have Investigated the Effect Of Visual Elmentioning
confidence: 99%
“…However, most of the research investigating the impact of Quizlet and podcasting on students' vocabulary acquisition has used investigator-created or available material. Relatively little has been done to study the benefits of studentcreated podcasts and Quizlet flashcards, despite the fact that various studies have demonstrated the cognitive, affective and motivational benefits accrued to students' creating their own learning material (Gholami & Mohammadi, 2015;Hsu et al, 2008;Milliner, 2013;Nikolova, 2002;Oberg, 2012;Philips, 2017;Wong & Looi, 2010). For example, Nikolova (2002) investigated how effective vocabulary acquisition is when students participate in the creation of the learning material.…”
Section: Various Researches Have Investigated the Effect Of Visual Elmentioning
confidence: 99%
“…All we can say at the moment is that accessibility looks like an important feature of a real vocabulary, and that this idea needs to be explored. Some interesting ideas about automaticity in an L2 are developed in Segalowitz and Gatbonton (1995), Segalowitz et al (1998), Segalowitz (2003), Oberg (2012), Miralpeix andMeara (2014), andPellicer-Sánchez (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Una dimensión muy importante del conocimiento del vocabulario es el conocimiento del vocabulario receptivo frente al productivo. En general, el vocabulario receptivo se conoce antes del vocabulario productivo, por lo tanto, la adquisición del vocabulario debe considerarse como un continuo, en el que una palabra pasa del estado receptivo al productivo (Oberg, 2012). Ambos vocabularios están relacionados y que el tamaño del vocabulario receptivo de los alumnos es mucho mayor que el tamaño del vocabulario productivo (Zhou, 2010).…”
Section: Figura 2 Frecuencia Y Tamaño De Vocabulario En La Enseñanza ...unclassified